Isoform-Selective HDAC Inhibitor Mocetinostat (MGCD0103) Alleviates Myocardial Ischemia/Reperfusion Injury Via Mitochondrial Protection Through the HDACs/CREB/PGC-1α Signaling Pathway. Issue 2 (February 2022) - Wang, Kaihao; Tang, Ruijie; Wang, Siyuan; Xiong, Yuyan; Wang, Wenyao; Chen, Guihao; Zhang, Kuo; Li, Ping; Tang, Yi-Da
Abstract: Over the past decade, histone deacetylases (HDACs) has been proven to manipulate development and exacerbation of cardiovascular diseases, including myocardial ischemia/reperfusion injury, cardiac hypertrophy, ventricular remodeling, and myocardial fibrosis. Inhibition of HDACs, especially class-I HDACs, is potent to the protection of ischemic myocardium after ischemia/reperfusion (I/R). Herein, we examine whether mocetinostat (MGCD0103, MOCE), a class-I selective HDAC inhibitor in phase-II clinical trial, shows cardioprotection under I/R in vivo and in vitro, if so, reveal its potential pharmacological mechanism to provide an experimental and theoretical basis for mocetinostat usage in a clinical setting. Human cardiac myocytes (HCMs) were exposed to hypoxia and reoxygenation (H/R), with or without mocetinostat treatment. H/R reduced mitochondrial membrane potential and induced HCMs apoptosis. Mocetinostat pretreatment reversed these H/R-induced mitochondrial damage and cellular apoptosis and upregulated CREB, p-CREB, and PGC-1α in HCMs during H/R. Transfection with small interfering RNA against PGC-1α or CREB abolished the protective effects of mocetinostat on cardiomyocytes undergoing H/R. In vivo, mocetinostat was demonstrated to protect myocardial injury posed by myocardial I/R via the activation of CREB and upregulation of PGC-1α. Mocetinostat (MGCD0103) can protect myocardium from I/R injury through mitochondrial protection mediated by CREB/PGC-1α pathway. Therefore, activation of the CREB/PGC-1α signaling pathway via the inhibition of Class-I HDACs may be a promising new therapeutic strategy for alleviating myocardial reperfusion injury.